Pola Pendidikan Inkulusif Studi Bagi Anak yang Mengalami Gangguan Komunikasi - Alwi Umar Batubara; Nanda Ayuningtyas; Rini Amelia Siagian; Jumi Laila Nurzannah (PKP Pusat Jurnal LPPM IAi Nasional Laaroiba, 2024)
Children with disabilities are children who have physical or mental deficiencies and have difficulty communicating in social environments, one of which is in the school environment. This research aims to find out what forms occur between teachers and students with special needs in inclusive schools. In communicating, teachers need to consider the characteristics of students with special needs to be able to determine the appropriate form of communication so that learning objectives can be achieved. This research uses a qualitative approach with descriptive methods. Research was conducted in elementary schools. The research results show that there are several factors that influence the form of teacher communication towards students with special needs. This research focuses on the communication patterns used by teachers in the teaching and learning process of children with disabilities. The diversity of developmental characteristics and obstacles they experience will lead to different communication models that we can present to them in helping them to carry out social interactions. The effectiveness of the communication that occurs with them really depends on the instruments they use to help them communicate with all their limitations.